Implementasi Kegiatan Fisik Pada Kegiatan Senam Untuk Menstimulasi Perkembangan Fisik Pada Anak Sekolah Dasar - Agus Mulyana; Dewi Sunengsih; Dini Alfiani; Hanif Khotimah; Sabrina Octaf Erina; Suci Aprillia; Syafira Rama Dhani Novianingsih (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Every child needs activities that are beneficial for their health. One of the activities that can be done is rhythmic gymnastics. This study uses the literature review method. A literature review is an approach in a traditionally conducted literature review with the aim of collecting and critically evaluating various reference sources related to the topic being discussed. Every child needs physical activity for their physical development later on, the factors that affect physical development in children are gross motor physical development where children are not yet able to perform body movement activities in coordination, lack of body flexibility and balance in the strength of the child's leg muscles. Children's motor development can be said to be mature if children have body skills and a healthy way of life, with this can support strong, healthy and skillful physical growth. The form of activities that can develop gross motor skills in children is to invite children to exercise one of them with this rhythmic gymnastics, with this the child can freely move all his limbs.